2012
DOI: 10.1371/journal.pone.0036592
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Related to White and Black Plumage Formation by RNA-Seq from White and Black Feather Bulbs in Ducks

Abstract: To elucidate the genes involved in the formation of white and black plumage in ducks, RNA from white and black feather bulbs of an F2 population were analyzed using RNA-Seq. A total of 2,642 expressed sequence tags showed significant differential expression between white and black feather bulbs. Among these tags, 186 matched 133 annotated genes that grouped into 94 pathways. A number of genes controlling melanogenesis showed differential expression between the two types of feather bulbs. This differential expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 59 publications
4
74
0
Order By: Relevance
“…Based on these results, although feathers are elaborate skin appendages, the mechanism for melanogenesis between skin and feather in black-bone chicken is significantly different. Li et al showed that the expression of TYR and MITF was associated with the formation of black and white plumage in ducks [58]. Melanin pigmentation is an important component of vertebrate colouration that is often under strong genetic control [3].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, although feathers are elaborate skin appendages, the mechanism for melanogenesis between skin and feather in black-bone chicken is significantly different. Li et al showed that the expression of TYR and MITF was associated with the formation of black and white plumage in ducks [58]. Melanin pigmentation is an important component of vertebrate colouration that is often under strong genetic control [3].…”
Section: Discussionmentioning
confidence: 99%
“…A fragment of β-actin that spans an intron sequence was used to verify the efficiency of the reverse transcription reaction and to exclude genomic DNA contamination. The primer sequences were as follows: forward primer, 5'-AACTGGGATGACATGGAGAAGA; and reverse primer, 5'-ATGGCTGGGGTGTTGAAGGT (Li et al, 2012).…”
Section: Rna Isolation and Reverse Transcriptionmentioning
confidence: 99%
“…Then, Solexa sequencing of the pooled RNA from the LPS-treated samples and the control samples was conducted at Shanghai Hanyu Bio-Tech (Li et al, 2012;Jiang et al, 2013). The Anase Duck database (ftp://ftp.plantbiology.msu.edu/pub/data/Eukaryotic_Projects/o_sativa/annotation_dbs/pseudomolecules/version_6.1/all.dir/) was employed for sequence analysis.…”
Section: Rna-seq Data Mining and Gene Ontology (Go) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomics is an important post-genomic era research field that not only studies gene expression and regulation, but also investigates gene functions. It is the foundation and starting point of investigations on the function and structure of genes (Jääger et al, 2012;Li et al, 2012;Sangwan et al, 2013). Single cell RNA-Seq technology is a powerful tool that can provide information about tens of thousands of genes from a single cell.…”
Section: Introductionmentioning
confidence: 99%